A STUDY OF SWEAR WORDS IN GLASS ONION: A KNIVES OUT MYSTERY (2022) - Razaq, Fadhil Firsan; Dahnilsyah, Dahnilsyah; Syarfi, M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to identify the types and the functions of swear words used by the characters in Rian Johnson’s movie entitled Glass Onion: A Knives out Mystery (2022). This study is conducted by using qualitative method and the findings are explained descriptively. Data were generated from the movie script, in the form of utterances, dialogues, and conversations that contain swear words. The findings revealed that the types of swear words in this movie are classified into four categories, those were epithet, profanity, obscenity and vulgarity. The results further indicates that there exist five categories of swearing based on its functions in this movie, there are cathartic swearing, emphatic swearing, abusive swearing, idiomatic swearing, and dysphemistic swearing. Afterwards, the results showed that the characters in this movie react differently to the dynamics that emerge from each conflict. Various emotions had seen throughout the scene, including astonishment, admiration, frustration, rage, regret, and others. This is what drives the characters in this movie to use various swear words as a means of expressing a range of emotions they experience while dealing with conflict in each scene. Keywords: swear word, swearing, movie